2009
DOI: 10.4103/0970-0218.51237
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sexual outcomes in primiparous women experiencing vaginal and caesarean births

Abstract: Background and Objective:We conducted this study to evaluate and compare postpartum sexual functioning after vaginal and caesarean births.Materials and Methods:This was a cross-sectional study that was carried out in postnatal health care in a hospital. A total of 50 primiprous women who had given birth 6-12 months ago and came to the hospital for postnatal care were asked to join the study. Forty of the women completed the entire questionnaire. Among these women, 20 delivered spontaneously with mediolateral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…The prevalence of FSD after childbirth has been reported to be 5-35% after caesarean section and 40-80% after normal vaginal delivery [11]. Australian research [12] showed that 64.3% of women experienced FSD and 70.5% sexual dissatisfaction during the first year after childbirth.…”
Section: Prevalence Of Female Sexual Dysfunction (Fsd) Postpartummentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of FSD after childbirth has been reported to be 5-35% after caesarean section and 40-80% after normal vaginal delivery [11]. Australian research [12] showed that 64.3% of women experienced FSD and 70.5% sexual dissatisfaction during the first year after childbirth.…”
Section: Prevalence Of Female Sexual Dysfunction (Fsd) Postpartummentioning
confidence: 99%
“…With the first pregnancy 40-70% of couples experience a drop in marital quality with marital conflict increasing, an increased risk of depression, individuals reverting to stereotypic gender roles, women being overwhelmed by childcare and housework, fathers withdrawing into work and decreased marital conversation and sexual activity [8]. And, 41-83% of couples still have difficulties at 2-3 months [9, 10].The prevalence of FSD after childbirth has been reported to be 5-35% after caesarean section and 40-80% after normal vaginal delivery [11]. Australian research [12] showed that 64.3% of women experienced FSD and 70.5% sexual dissatisfaction during the first year after childbirth.…”
mentioning
confidence: 99%
“…Twenty-one patients with a history of severe preeclampsia, [14] patients with a history of eclampsia and 18 patients with a history of major hemorrhage were included in the study group ( Figure 1). Their fear of getting pregnant again, sexual functions and fear of death during the last delivery were measured by questionnaires.…”
Section: J Clin Exp Invest Wwwjceionlineorg Vol 4 No 4 December 2013mentioning
confidence: 99%
“…In literature, there are several studies assessing the postpartum sexual functions after cesarean [13,14]. Considered in terms of the mode of delivery, the cesarean is more protective for sexual functions compared to the normal vaginal delivery [1].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Immediate postpartum IUCD insertion is approved by WHO, as one of the safe and effective method of temporary contraception. 6 In the immediate post delivery period the women are highly motivated and need an effective method for contraception so that the child can be brought up with a relaxed mind without the worry of unintended pregnancy.…”
Section: Introductionmentioning
confidence: 99%